New Design of Encryption with Covertext and Reordering - Eka Ardhianto; Widiyanto Tri Handoko; Hari Murti; Rara Sri Artati Redjeki (Universitas Kristen Satya Wacana, 2023)
Documents for some entities are confidential and important, so security is required. Encryption with Covertext and Reordering (ECR) is a text-based document security model. ECR uses a random key to generate the ciphertext. The ECR’s random key is selected using the human-generated method. This research aims to increase the level of document security based on the ECR mechanism. This paper proposes a new method by using a random key in a permutated table. The random key is generated automatically by a function. The entropy is used as a measurement of the security level of the encrypted documents. The experimental shows that the permutated table inside the ECR provides better entropy values. It implies a better security level. The use of permutated tables also makes it easier to use ECR to secure documents.